Frequency Of Pneumonia 01 To 05 Years Age Of Children Presenting With Measles (Journal of Pharmaceutical Negative Results, 2021)
Introduction: Most measles fatalities come from complications. As many as 40% of measles patients develop complications, which are enhanced by extreme age and underlying factors including malnutrition. Measles-related fatalities are most often caused by pneumonia, 56–86%.Objectives: Determine Measles-related pneumonia frequency in children.Study Design: Descriptive, Cross-sectional study.Duration and Place of the Study: Department of Pediatric Medicine, Ayub Teaching Hospital, Abbottabad Study Duration: 22nd July 2020 to 21st January 2021.Materials & Methods: The study included 96 children aged 1–5 with Measles of either gender. Tuberculosis-related pneumonia was ruled out. Every kid who meets the inclusion requirements has their age, sex, address, weight, and other information recorded on a proforma. An experienced CPSP pediatrician fellow supervised all clinical observations.Results: The age range in this study was 1-5 years, with a mean age of 3.48 ± 1.05 years. The majority of 49 (51.04%) patients were 1-3 years age. Out of 96 patients, 66 (68.75%) were male and 30 (31.25%) were female, a 2.2:1 ratio. The present study identified 55 (57.29%) Measles-presenting children with pneumonia.Conclusion: This study concluded that the frequency of pneumonia in children presenting with Measles is very high.